Generic and vision related quality of life associated with different types of cataract surgeries and different types of intraocular lens implantation - Shalu Jain; Akshay Chauhan; Kavitha Rajshekar; Praveen Vashist; Promila Gupta; Umang Mathur; Noopur Gupta; Vivek Gupta; Parul Dutta; Vijay Kumar Gauba; James Fielding Hejtmancik (PLoS ONE, 2020)
Objectives To assess the effects of different types of cataract surgeries and intraocular lenses on generic as well as vision related quality of life of cataract patients, using EQ-5D and IND-VFQ 33 instruments respectively. Methods An observational, longitudinal study of patients undergoing cataract surgery was carried out at three ophthalmology centres. Patients were prospectively admitted for surgery for age-related cataract. Generic quality of life was assessed by using Euroqol’s EQ5D-5L questionnaire and vision related quality of life was assessed by the IND-VFQ-33 questionnaire. Data pertaining to vision function and quality of life were collected pre surgery and 4 weeks after the surgery. Results Out of total patients (n = 814) recruited for the study, 517 patients were interviewed for both pre-surgery and post-surgery for EQ5D and 519 patients were interviewed for both pre-surgery and post-surgery for IND VFQ 33 tool. The combined data from all three centres showed that Quality Adjusted Life Year (QALY) gains observed in patients undergoing phacoemulsification with foldable lens implantation (2.25 QALY) were significantly higher (0.57 QALY) as compared to Small Incision Cataract Surgery (SICS) with PMMA lens implantation (1.68 QALY). Highest improvement however, in all three subscales of IND-VFQ-33 tool were clearly observed for SICS with PMMA lens implantation. Conclusions The study has elicited the Health related and vision related Quality of Life scores for cataract surgeries and subsequent lens implantation. This study also offers Health State Utility Values along with visual outcomes for different surgical procedures, lenses and for the combination of surgery with lens implantation for cataract procedures providing a useful resource for future economic evaluation studies.